Damage monitoring on carbonate stones: Field exposure tests contributing to pollution impact evaluation in two Italian sites. (15th October 2017) - Comite, V.; Álvarez de Buergo, M.; Barca, D.; Belfiore, C.M.; Bonazza, A.; La Russa, M.F.; Pezzino, A.; Randazzo, L.; Ruffolo, S.A.
Highlights: A field exposure test in two different urban environments is proposed. The effect of urban air pollution on three different stones was assessed. Physical features of stones affect the susceptibility to capture particulate. Trace element concentrations provide information about pollution sources. Abstract: During the last decades, many studies have been carried out on environmental monitoring in specific sites aiming at their protection and conservation; however, researches focused on the direct implications, in terms of quantitative evaluation of stone deterioration, of these monitoring actions are still scarce. This experimental work aims at monitoring the degradation processes affecting historical buildings constituted by carbonate stones. Specifically, specimens of Carrara marble and two limestones largely used in the Sicilian Baroque architecture, namely Noto and Comiso stones, were exposed outdoor in two Italian sites (Catania and Palermo), which are characterized by different environmental conditions. The field exposure test lasted two years. Both the substrates and the deposited particulate collected at the end of the exposure underwent several analytical investigations including: i) optical microscopy, mercury intrusion porosimetry, colorimetric analysis and roughness analysis, for the characterization of stone substrates before exposure; ii) ion chromatography (IC), infrared spectroscopy analysis (FT-IR) and inductively coupled plasma mass spectrometry (ICP-MS), for the characterization of the particulate deposited on stone surfaces. The obtained results highlighted blackening and yellowing processes of the carbonate substrates, chiefly on those specimens exposed in Palermo where such processes were more noticeable. Furthermore, the high concentration of sulphates and heavy metals detected (mainly in Palermo site) pointed out that both cities are mainly interested by mobile emission sources such as vehicular traffic. Additionally, analyses demonstrated the key-role of intrinsic features of the lithotypes in the degradation processes. In this regard, the higher porosity and surface roughness of Noto stone explains the major deposition of particulate with respect to the other two examined carbonate rocks.